Encyclopedia of detail in contemporary residential architecture - McLeod, Virginia (London, United Kingdom : Laurence King Publication, 2010)
This is a comprehensive sourcebook, containing newly commissioned scale drawings of every type of architectural detailtaken from 100 of the best contemporary houses. Over 700 detailed drawings of walls, floors, ceilings, doors, windows, and staircases feature keys explaining construction techniques and materials used. Each drawing is cross referenced to other details from the same building. This is an invaluable reference for all architects, showing the best examples of residential detailing from around the world.
1. Concrete houses -- 2. Glass houses -- 3. Masonry houses -- 4. Steel house -- 5. Timber houses.
Keywords: ARCHITECTURE, DOMESTIC -- DESIGNS AND PLANS